PENGARUH PENGGUNAAN BINDER TERHADAP KEPEKATAN WARNA MENGGUNAKAN PIGMEN THERMOCROMIC LEUCO DYE PADA MATERIAL PRODUK FASHION KULIT (LEATHER) - Junaidi Salam (Narada : Jurnal Desain dan Seni, 2021)
Thermochromic Dye is a substance that changes color due to temperature changes. Leuco Dye itself is a compound that is colorless or weakly colored, and reacts with the developer, to turn into a animate state. Thermocromic staining will experience a color change phenomenon when it receives a higher temperature change. The molecules contained in the substance will change into other color molecules when exposed to heat, but when the temperature drops again (cools down) the color changes again or looks transparent or another color. The application of a base coat in the finishing process is important because it greatly affects the physical properties of the skin. The materials used to make the base layer include binders, pigments, and solvents. The number of pigments and binders used in the finishing process varies, so the resulting skin has different qualities. This quality inconsistency is one of the problems in finishing the skin because there is no definite knowledge about the amount of binders and pigments that are applied to various types of skin. In the application of this color, of course, a binder is needed that is able to carry the croma substance attached to the material being applied. Thermocromic color pigment testing was carried out by comparing the use of protein and synthetic (acrylic) binder types in the leather material. With the treatment of cold and hot temperature discoloration, the result is that the use of acrylic binder experiences a constant change for ± 3 second / 10C a decrease in cold temperature in the slow reaction test, and a ± 5 second / 7.50 C increase in hot temperature in the slow reaction test. So that it shows colors at cold temperatures last longer at room temperature than colors at hot temperatures. While the use of protein binders shows a ± 5 second / 7.50C decrease in cold temperature in the slow reaction test and a ± 5 second / 7.50C increase in heat in the slow reaction test, but the color characters are not completely bound by the protein binder and still release the pigment to dust (dust), so the use of acrylic binders using acetone solvent is better than protein binders